A critical review of CO2 enhanced oil recovery in tight oil reservoirs of North America and China. (15th September 2020) - Song, Zhaojie; Song, Yilei; Li, Yuzhen; Bai, Baojun; Song, Kaoping; Hou, Jirui
Highlights: A comprehensive literature review was conducted on CO2 -EOR in tight oil reservoirs. Specialized technologies are needed in the exploitation of China's tight reservoirs. The effect of CO2 diffusion is relatively exaggerated in experimental results. CO2 -crude oil interaction in nanopores may lead to an oil recovery increment. CO2 -water-minerals interaction influences the geomechanical properties of rock. Abstract: Primary oil recovery remains less than 10% in tight oil reservoirs, even after expensive multistage horizontal well hydraulic fracturing stimulation. Substantial experiments and simulation works have been performed to investigate CO2 enhanced oil recovery (CO2 -EOR) potential in tight reservoirs; however, some results conflict with each other. The objectives of this paper are to fully understand the CO2 -EOR mechanisms and to figure out the difference between tight oil exploitation in North America and China through a comprehensive literature review. It is shown that compared with Bakken and Eagle Ford formation, China's tight oil reservoirs feature higher mud content and oil viscosity while they have a lower brittleness index of rock and formation pressure coefficient, leading to confined stimulated reservoir volume and further limited CO2 -oil contact. The effect of CO2 molecular diffusion is relatively exaggerated in experimental results, which can be attributed to the dual restrictions of exposure time and oil-CO2 area in field scale. Numerical simulation works show that the shifted phase properties in nanopores lead to an oil recovery increment. The development of nano-scale chips withholding high pressure/temperature may advance the experimental study on the nanopore confinement effect. CO2 -fluid-rock minerals interaction might be more complex due to the large specific surface area of nanopores in tight formations. The geomechanics coupling effect cannot be ignored when examining the CO2 -EOR performance in tight reservoirs. And a comprehensive simulation study coupling with technical and economic feasibility is highly recommended before running a field test of CO2 -EOR.